The voice of a child in family law disputes - Parkinson, Patrick; Cashmore, Judy. (Oxford : Oxford University Press, 2008)
Is it better to keep children out of family law conflicts about parenting, or to give them a say? This book integrates the issues with empirical data on the views and experiences of children and other participants in such disputes, suggesting ways that children can better be heard without placing them at the centre of conflicts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Parent and child (Law); Children -- Legal status, laws, etc; Custody of children; Domestic relations courts; Children's rights